Faith and Freedom: Muslim Women Between Tradition and Modernity in Leila Aboulela'sMinaret - Moulati Oumaima; Dou Safa (University of Eloued جامعة الوادي, 2025)
يدرس هذا البحث التحول الذي تمر به نجوى، المرأة العربية المسلمة في المملكة المتحدة، كما تصورها رواية ليلى أبو العلا "المنارة"(2005). في مواجهة الاغتراب الثقافي والانسلاخ عن الهوية، تعتمد نجوى على إيمانها الإسلامي لإعادة بناء ذاتها، مستعيدة بذلك تمكينها وقدرتها على الفعل. يتوافق هذا البحث مع الهدف الأدبي الأوسع لأبو العلا في تفنيد الصور النمطية الغربية عن المرأة العربية، حيث يُصوَّر الإسلام كمصدر لقوة وليس كمصدر للقمع.من خلال منهج تحليلي، تبحث هذه الدراسة تطور شخصية نجوى، مع التركيز على علاقاتها الاجتماعية في سياق الشتات وصحوتها الروحية. كما تسلط الضوء على هويتها الهجينة التي تجمع بين تراثها السوداني وتجاربها الغربية. بالإضافة إلى ذلك، يتناول البحث الأساليب السردية التي تستخدمها أبو العلا، والتي تعكس موقعها ككاتبة مهاجرة، لتصوير رحلة نجوى المعقدة.في النهاية، يجادل البحث بأن الهجينة الروحية والثقافية لنجوى تتحدى السرديات الغربية السائدة، مقدمة فهمًا دقيقًا للتمكين والانتماء عبر الإسلام. وبذلك، تسهم الدراسة في النقاش الأوسع حول الهويات المتعددة الأبعاد للمرأة المسلمة في الشتات ودور الإيمان في اكتشافها لذاتها وصمودها. This study examines the transformational journey of Najwa, an Arab Muslim woman in the UK, in Leila Aboulela’s 2005 novel Minaret. Facing cultural dislocation and alienation, Najwa turns to her Islamic faith as a means of rebuilding her identity, finding empowerment, and reclaiming agency. The research aligns with Aboulela’s broader literary goal of challenging Western stereotypes about Arab women by portraying Islam as a source of strength rather than oppression. Through an analytical lens, the study explores Najwa’s character development, emphasizing her evolving social relationships in a diasporic setting, her educational growth, and her spiritual awakening. It highlights how she negotiates a hybrid identity, balancing her Sudanese heritage with her Western experiences. Additionally, the study investigates Aboulela’s narrative techniques, which reflect her own position as a diasporic writer, to depict Najwa’s complex journey. Thus, the research argues that Najwa’s spiritual and cultural hybridity resists dominant Western narratives, offering a deep understanding of empowerment and belonging through Islam. By doing so, the study contributes to broader discussions on the distinctive identities of Muslim women in diaspora and the role of faith in their self-discovery and resilience.
Master's Degree In Literature and Civilization
Keywords: الإيمان، الهوية، التقاليد، الحداثة، التهجين، الشتات